2008
DOI: 10.1021/jm701428b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Novel Pyrido[1,2,3-de][1,4]benzoxazine-6-carboxylic Acid Derivatives Carrying the 3-Cyclopropylaminomethyl-4-substituted-1-pyrrolidinyl Group as a C-10 Substituent

Abstract: Novel pyrido[1,2,3- de][1,4]benzoxazine-6-carboxylic acid derivatives 5- 9 carrying a 3-cyclopropylaminomethyl-4-substituted-1-pyrrolidinyl moiety at the C-10 position were synthesized and their in vitro antibacterial activity, intravenous single-dose toxicity, convulsion inductive ability, and phototoxicity were evaluated. It appeared evident that compounds 5a, 6a, 8a, and 9a, which have a cis-oriented 4-methyl or 4-fluoro-3-cyclopropylaminomethyl-1-pyrrolidinyl moiety at the C-10 position, exhibited 2- to 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Some of the clinical used FQs such as OLFX, LVFX and levonadifloxacin have a six‐membered ring connecting the N‐1 to C‐8 position, so this kind of six‐membered ring is worth to be further investigated. To explore more effective antibacterials, ten 4‐quinolone derivatives 4 that have an oxygen‐fused ring connecting the N‐1 to C‐8 position were screened for their in vitro and in vivo antibacterial activities against drug‐sensitive and quinolone‐resistant strains . The SAR suggested that compared with –H derivatives 4a – e , introduction of –F at six‐membered ring 4f – j boosts up the activity against Gram‐negative pathogens.…”
Section: Structure–activity Relationshipmentioning
confidence: 99%
“…Some of the clinical used FQs such as OLFX, LVFX and levonadifloxacin have a six‐membered ring connecting the N‐1 to C‐8 position, so this kind of six‐membered ring is worth to be further investigated. To explore more effective antibacterials, ten 4‐quinolone derivatives 4 that have an oxygen‐fused ring connecting the N‐1 to C‐8 position were screened for their in vitro and in vivo antibacterial activities against drug‐sensitive and quinolone‐resistant strains . The SAR suggested that compared with –H derivatives 4a – e , introduction of –F at six‐membered ring 4f – j boosts up the activity against Gram‐negative pathogens.…”
Section: Structure–activity Relationshipmentioning
confidence: 99%
“…另外一些包含 3-氟吡咯烷结构的化合物还具有良好的抗菌活性(图 3, III) [20] . 我们课题组研究发现邻碘苯磺酸钠/Oxone 氧化体 系可在无过渡金属参与条件下高效地实现苄位碳氢键 氧化.…”
Section: -氟吡咯烷是一类重要的含氮杂环结构单元 存在unclassified
“…8) Less effort has been focused on the manipulation of the temperature and vacuum pressure when drying the APIs, which can affect the polymorphic properties of the API. 9) To ensure an uninterrupted supply of 006, we describe the development of a multi-kilogram scale linear synthetic route and crystallization process.…”
Section: Introductionmentioning
confidence: 99%